MENINGKATKAN HASIL BELAJAR SISWA MELALUI MEDIA ULAR TANGGA MATERI OPERASI HITUNG BILANGAN CACAH KELAS V - Sri Nurhalimah; Budiyono; Khoirul Fansuri; Agus Sumarliani; Marilowati (STKIP Subang, 2024)
The purpose of this study is to increase the learning outcomes of students of grade V SDN Gading VII Surabaya on the material for counting numerical numbers up to 100,000 through the use of snakes and ladders media. This classroom action study applies a problem-based learning model, consisting of two cycles, in which each cycle includes the stages of planning, implementing actions, observing, and reflecting. The results of this study show a significant improvement in student's learning outcomes in each cycle. In the pre-cycle, there are only 47% of students achieved completeness with an average score of 70, but in the first cycle, the completeness increased to 80% with an average score of 80, and in the second cycle it reached 90% with an average score of 86. These increases show that the use of Snakes and Ladders media is effective in motivating students, increasing active participation, and improving student learning outcomes. Furthermore, the Snakes and Ladders media has also proven to be successful in creating a pleasant and interactive learning atmosphere, as well as in developing social skills and cooperation among students.